Pelaksanaan Akad Nikah Secara Virtual pada Masa Pandemi: Analisis Empat Mazhab - Arif, Alfiani; Talli, Abdul Halim; Ramli, Arif Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This article discusses the law of carrying out online marriage during the pandemic (analysis of four schools of thought). In answering these problems and analyzing qualitative data, the author uses a normative juridical approach. This research is classified as library research, this type of research is to analyze the content (content analysis) that is in accordance with the problems discussed, then review and conclude it. Researchers found: online marriage is a form of marriage in which the consent transaction is carried out through circumstances or activities that are connected to a network or internet system (via online), between the prospective groom and the bride, the guardian and the witness are not in one place but in the same place. displayed is only a form of visualization from both parties through the help of electronic tools (online media). The implementation of online marriage in Indonesia according to the law and analysis of the four schools of thought is allowed on the condition that its implementation must be in accordance with the pillars and conditions of marriage in general and under certain (urgent) circumstances.